Assessment of serum levels of monocyte chemoattractant protein 1 (MCP 1) in patients with periodontitis and atherosclerotic cardiovascular disease - Safa A Hamad; Maha S Mahmood (College of Dentistry/ University of Baghdad, 2022)
Background: Monocyte chemotactic protein-1 (MCP-1) is a chemokine expressed by inflammatory and endothelial cells. It has a crucial role in initiating, regulating, and mobilizing monocytes to active sites of periodontal inflammation. Its expression is also elevated in response to pro-inflammatory stimuli and tissue injury, both of which are linked to atherosclerotic lesions. Aim of the study: To determine the serum level of MCP-1 in patients with periodontitis and atherosclerotic cardiovascular disease in comparison to healthy control and evaluate the biomarker's correlations with periodontal parameters. methods: This study enrolled 88 subjects, both males and females, ranging in age from 36-66 years old, and divided into four groups: 1ST group with atherosclerotic cardiovascular disease (ASCVD) without periodontal disease (25 patients), 2nd group with periodontitis and systemically healthy, (25 patients),3rdgroup having both ASCVD and periodontitis (25 patients), and the 4th is the control group without any systemic disease and with good oral hygiene (13 subjects). The clinical periodontal parameters plaque index (PL I), Bleeding on probing (BOP), Probing Pocket depth (PPD) and clinical attachment level (CAL) were used to evaluate periodontal health status. Atherosclerotic cardiovascular disease patients were chosen after clinical examination by specialists and diagnoses confirmed with catheterization. Following clinical assessment, 5ml of venous blood was drawn from each participant MCP-1 levels in the blood were then measured using enzyme-linked-immunosorbent assay (ELISA). Results: According to the findings of this study, the mean values of PLI and BOP were higher in periodontitis group and athero+periodontitis group than in athero group and control group, PPD and CAL mean values were greater in athero+periodontitis group than in periodontitis group. The serum level of MCP-1 was higher in athero+periodontitis group than in athero, periodontitis and control groups. Regarding the correlations between MCP-1 and clinical periodontal parameters. In periodontitis group there was a positive correlation with PPD and CAL and there was a positive correlation with CAL in athero+periodontitis. Conclusion: This study revealed that periodontitis with higher MCP-1 level may be linked to an increased risk of atherosclerosis.